Rewiring the Apparatus: Screen Theory, Media Activism, and Working-Class Subjectivities. Issue 1 (2nd January 2016) - Robé, Chris; Wolfson, Todd; Funke, Peter N.
Abstract : This essay utilizes concepts from screen theory to better understand the function of socially engaged documentaries. In particular, it explores how the media practices of the Media Mobilizing Project (MMP) allow us to refocus our analysis to take account of the utilization of media by social movements in ways that stress the collective and empowering role it can have for fostering class-based identities. As such, we aim to highlight the materiality of ideology and the possibility of collective class-based political projects that employ various film and media practices. MMP's video work indicates opportunities for employing video to establish broader working-class subjectivities. We hold that utilizing screen theory accordingly helps to augment our understanding of activist documentary forms. Moreover, linking activist documentary forms with the media practices of contemporary social movements allows us to gain a newfound appreciation for the emancipatory role of media as such.